Thermochemical conversion of biomass to liquid fuels and chemicals - Crocker, Mark (RSC energy and environment series ;, 2010)
There is increasing recognition that low-cost, high capacity processes for the conversion of biomass into fuels and chemicals are essential for expanding the utilization of carbon neutral processes, reducing dependency on fossil fuel resources, and increasing rural income. While much attention has focused on the use of biomass to produce ethanol via fermentation, high capacity processes are also required for the production of hydrocarbon fuels and chemicals from lignocellulosic biomass. In this context, this book provides an up-to-date overview of the thermochemical methods available for bioma.